HOMONYMOUS RELATIONS IN COMPOUND WORDS IN ENGLISH AND UZBEK LANGUAGES - O‘ktamova Malika Dilmurod qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This paper explores the phenomenon of homonymous relations in compound words in English and Uzbek languages. Homonymy, which refers to words that are identical in form but differ in meaning, plays a significant role in the structure and interpretation of compound words. The study compares the formation, usage, and semantic diversity of compound homonyms in both languages, highlighting similarities and differences influenced by linguistic, cultural, and cognitive factors. Through qualitative analysis and selected examples, the research identifies common patterns and unique cases where compound words demonstrate homonymous features. The findings contribute to a deeper understanding of lexical ambiguity and semantic structure across typologically distinct languages, providing valuable insights for comparative linguistics, translation studies, and language teaching.